Pendampingan Sertifikasi Halal Gratis bagi Pelaku Usaha Mikro dan Kecil di Kabupaten Tanjung Jabung Timur - Mohd. Norma Sampoerno; Maratun Saadah; Turino Adi Irawan; Sean Popo Hardi; Achyat Budianto (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The process of digitizing halal certification turns out to be quite difficult for business actors who are not familiar with using computers. Moreover, it takes a long time to fill out the entire form, micro and small business actors who do not have employees prefer to open a business or operate as usual rather than spending time studying a series of certification processes. Therefore, the writing team as halal assistants feel the need to carry out community service in the form of assistance in filling out forms (SJPH). Based on the results of the dedication that has been carried out, it can be said that the service activities have been successful, business actors understand the importance of halal certificates, consciously and willingly attend the mentoring event to gain technical knowledge of processing halal certificates. Business actors are also willing to make improvements when during the filing period a discrepancy is found by the fatwa commission which must be corrected by the business actor.